PENGARUH KEPEMIMPINAN TRANSFORMASIONAL PADA KETERLIBATAN KERJA DALAM ORGANISASI PERUBAHAN - Desti Shalsabila; Danang Nugroho; Nisa Fauziah; Muhammad Rizaldy; Aldi Ramadhan; Mochammad Yogie Alamsyah Gunawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Members and leaders are still necessary in organizations today. Leaders are essential in the operation of an organization as they are responsible for creating the vision, mission, and goals of the organization as well as organizing and directing staff members to work according to the leader's direction. However, leadership is not always easy. Leaders face many challenges, especially after the COVID-19 pandemic era ended. Due to such events, employees or members of the organization are unstructured. Therefore, in order for an organization to survive, transformational leadership is needed, especially those in companies. In addition, this transformational leadership role can increase employee engagement and encourage them to continue working hard. This research was conducted with a literature study research methodology, with five journals and theoretical books as reference data. The author found from the analysis of the reference journals that employee performance and their work engagement can be influenced by the transformational leadership style applied by each organization. Based on the research conducted, it can be concluded that transformational leadership has a positive impact on the performance of company organizational members. In addition, transformational leadership allows employees to be more innovative, creative, and loyal to the company.